Harlan Ellison's 7 against chaos - Ellison, Harlan (DC Comics, 2013)
In a distant future, Earth is in grave danger: The fabric of reality itself in unraveling, leading to catastrophic natural disasters, displaced souls appearing from bygone eras, and sudden, shocking cases of spontaneous combustion. The only hope for Earth's survival is a force of seven warriors, each with his or her special abilities. But can these alien Seven Samurai learn to get along in time to find the source of the gathering chaos and save all of reality?